1972
DOI: 10.1002/1097-0142(197206)29:6<1563::aid-cncr2820290620>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Ewing's tumor in children at Roswell Park Memorial Institute

Abstract: Twenty pediatric patients with Ewing's tumor seen at Roswell Park Memorial Institute, from 1954 to 1970, have been analyzed. Three patients are considered as cures. As the initial treatment, these three patients were all treated with radiotherapy to the primary tumor and adjuvant chemotherapy. Nine of the 20 patients were treated in this fashion. It was felt that the chemotherapy eradicated the subclinical micrometastasis and thus effected a cure. Five cases with reactivation of primary sites prior to, or simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…ranging from 12 to 73 cases (totaling 537 cases) of this cancer[8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…ranging from 12 to 73 cases (totaling 537 cases) of this cancer[8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Eight patients presenting with metastatic disease had complete responses to T-2 chemotherapy, but 7/g with metastatic disease eventually had tumor recurrence. Examination of the treatment failures, both those patients relapsing after adjuvant chemotherapy for primary Ewing's sarcoma (5), and those relapsing after having a complete response of metastatic disease (7) to T-2 chemotherapy, revealed that all relapses occurred at the end of the second year of T-2 chemotherapy o r after chemotherapy was stopped. In addition, of 23 patients receiving "curative" radiation therapy to their primary tumor, 5 had local recurrence (22%) and 6 (26%) had severe functional debility secondary to combined radiation therapy and T-2 chemotherapy.…”
mentioning
confidence: 99%